Review Importance of Herbal Plants in the Management of Urolithiasis: Review: Herbal Plants for Urolithiasis - Mansoor, Muhammad; Jamil, Muhammad; Latif, Noman; Muhammad, Sher; Gull, Jaweria; Shoab, Muhammad; Khan, Arsalan (Biological Sciences - PJSIR, 2019)
Medicinal plants have been known for millennia and are highly esteemed across the world as an abundant source of therapeutic agents for prevention of various ailments. Today large number of population is suffering from urinary calculi, kidney stone and gall stone. Stone disease has gained increasing relevance as a consequence to changes in living conditions, due to malnutrition and industrialization. Changes in incidence and prevalence, the occurrence of stone types and stone location, and the way in which stone removal are explained. Therapeutic plants (Armoracia lopathifolia, Cassia fistula, Diospyros melaoxylon etc.) are being used from centuries because of its safety, efficacy, ethnical acceptability and less side effects when compared with synthetic drugs. The present review deals with options to be followed for the potential of medicinal plants in stone dissolving activity.